The Effectiveness of Implementing Debt To Equity Swap as A Strategy For Performance Improvement and Non-Performing Loan Reduction - Prasetiyono, Didik (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to evaluate the effectiveness of credit restructuring through Debt Equity Swaps (DES) as a strategy to reduce non-performing loans (NPLs) at PT SIER Puspa Utama, a subsidiary of PT SIER Surabaya. The research adopts a qualitative descriptive approach, utilizing observation and field data. Data were collected using interviews and documentation techniques. The data analysis involved qualitative methods to assess the restructuring strategies' effectiveness. The study reveals that PT SIER Puspa Utama faced significant financial difficulties due to improper credit management, leading to a substantial portion of operational capital becoming NPLs. These challenges hindered the company's ability to operate optimally, posing risks of business failure and impacting shareholder confidence. As part of a credit restructuring strategy, the implementation of DES effectively addressed these issues. The restructuring allowed the conversion of bad debts into share capital, improving financial stability and reducing NPL levels. The findings underscore the importance of strategic financial management in corporate sustainability. For companies facing similar challenges, DES can be a viable solution for mitigating financial distress and restoring operational efficiency. This study highlights the need for robust internal policies and strategic planning to manage credit risks and maintain investor confidence.